Variation of δ18O in otoliths of Stellifer lanceolatus and Eucinostomus gula environmental change indicator in Terminos Lagoon, Mexico. (October 2020) - Dorantes-Hernández, J.M.; Torres-Rojas, Y.E.; Aguíñiga-García, S.; Ramos-Miranda, J.; Trasviña-Carrillo, L.D.; Flores-Hernández, D.; Sánchez-González, A.
Abstract: Environmental changes have been associated with natural climatic variability or human activity. Water resources management is, perhaps, the most drastic change observed in the coastal environment. However, external forcings such as the El Niño event have important implications in the global and regional hydrological balance. These environmental changes have an impact on the density and biomass of the ichthyofauna in the Terminos Lagoon (TL) for the past 30 years, presumably, associated with variations in the temperature and surface salinity of the sea. Therefore, in the present study, δ 18 O was quantified in otoliths of two important species due to their dominance: Stellifer lanceolatus and Eucinostomus gula, and to understand the environmental changes reflected in both species. The δ 18 O was analyzed in otoliths of these two species captured in 1998/1997, 2006/2007 and 2016/2017 and were compared with in situ temperature and salinity data. Sea surface temperature and salinity increased by 2 °C and 9, respectively, between 1997 and 2017. Stellifer lanceolatus δ 18 O values was in isotopic equilibrium with seawater calcite; while, E. gula is not in isotopic equilibrium. The δ 18 O of S. lanceolatus and E. gula varied significantly with the increase in salinity (R 2  = 0.8987 and R 2  = −0.2964) and not with the sea surface temperature. S . lanceolatus is an excellent bioindicator of changes in sea surface salinity in this region of the Gulf of Mexico. Highlights: δ 18 O in Stellifer lanceolatus was in isotopic equilibrium with seawater calcite. δ 18 O in Eucinostomus gula wasn't in isotopic equilibrium with seawater calcite. δ 18 O of both species varied significantly with the increase in salinity. S . lanceolatus is an excellent bioindicator of changes in salinity.